2010
DOI: 10.1002/chem.201001136
|View full text |Cite
|
Sign up to set email alerts
|

Non‐covalent Versus Covalent Control of Self‐Assembly and Chirality of Nile Red‐modified Nucleoside and DNA

Abstract: A DNA-based covalent versus a non-covalent approach is demonstrated to control the optical, chirooptical and higher order structures of Nile red (Nr) aggregation. Dynamic light scattering and TEM studies revealed that in aqueous media Nr-modified 2'-deoxyuridine aggregates through the co-operative effect of various non-covalent interactions including the hydrogen bonding ability of the nucleoside and sugar moieties and the pi-stacking tendency of the highly hydrophobic dye. This results in the formation of opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
62
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 80 publications
5
62
0
2
Order By: Relevance
“…Thus, the Watson–Crick base pairing of the corresponding modified oligonucleotides should be maintained. Over the past few years we have synthetically attached various chromophores, such as ethynylpyrenes [4445], BODIPY [46], ethynyl nile red [4748] and others, to 2’-deoxyuridines for electron transfer studies and for fluorescent probes. To gain greater insight into the counterbase selectivity, we performed PEX experiments with a representative set of chromophore-modified oligonucleotides and found that the DNA-polymerase-catalyzed nucleotide incorporation opposite to attached chromophores at the 5-position of uridine follows Watson–Crick selectivity [49].…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the Watson–Crick base pairing of the corresponding modified oligonucleotides should be maintained. Over the past few years we have synthetically attached various chromophores, such as ethynylpyrenes [4445], BODIPY [46], ethynyl nile red [4748] and others, to 2’-deoxyuridines for electron transfer studies and for fluorescent probes. To gain greater insight into the counterbase selectivity, we performed PEX experiments with a representative set of chromophore-modified oligonucleotides and found that the DNA-polymerase-catalyzed nucleotide incorporation opposite to attached chromophores at the 5-position of uridine follows Watson–Crick selectivity [49].…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the ethynyl nile red nucleoside 41 tends to aggregate in left-handed helicity, whereas DNA modified with five nucleosides of the type 41 forces the nile red chromophore to interact in a right-handed fashion. 101 …”
Section: Methodsmentioning
confidence: 97%
“…Andererseits,d .h.m it zunehmender Menge an Py--dU in den Aggregatmischungen, werden die reinen Nr--dU-Stapel durch Py--dU unterbrochen, was das Absorptionsmaximum von 559 nm (typisch für Nr--dUStapel) [18] nach 622 nm (typisch für Nr--dU-Monomere) verschiebt. [7b,8] Obwohl die genaue Sequenz der beiden Nucleoside entlang des (dA) 20 -Templats nicht bestimmt werden kann, schließen diese beschriebenen Beobachtungen ausgedehnte Stapel bestehend aus auschließlich Py--dU oder auschließlich Nr--dU aus und lassen uns annehmen, dass insbesondere in den Mischungen Py--dU:Nr--dU = 16:4 bis 4:16 gut gemischte Chromphorsequenzen aufgebaut werden.…”
Section: Methodsunclassified
“…Das Nr--dU-typische CD-Signal besteht aus einem positiven Cotton-Effekt, gefolgt von einem negativen CottonEffekt und einem Nulldurchgang bei ungefähr 560 nm, was dem Absorptionsmaximum der Nr--dU-Stapel entspricht. Verglichen mit dem publizierten Spektrum eines kovalent angeknüpften und dadurch rechtsgängig helikalen Stapels von Nr--dU in DNA [18] ist die Chiralität des nicht-kovalenten Aggregats entlang von Fulleren-(dA) 20 gegensätzlich, also linksgängig.¾ hnliche CD-Effekte wurden auch für Py--dU beobachtet, hauptsächlich in Aggregaten mit hçherem Py--dU-Gehalt. Mit ansteigender Menge an Nr--dU in den Aggregaten (angefangen bei Py--dU:Nr--dU = 12:8) verändert sich das CD-Signals für Py--dU kontinuierlich vom reinen Excitonsignal zum Signal für Furchenbindung.…”
Section: Methodsunclassified